Better together for better dementia research and care. - Lovestone, S; Rossor, M; Gallacher, J; Ritchie, C; Burn, D; Hyslop, P; Mackay, C; Matthews, P; Ballard, C; Georges, J (Lancet, 2016)
As professionals concerned for people with dementia today and dedicated to finding more effective treatment and prevention for dementia tomorrow, we value our membership of the European Union (EU) and are deeply concerned by the prospect of the UK exiting. The EU has made dementia research a priority and has made substantial funds available for research that is driving faster, more effective clinical trials that are our best hope of finding a disease-modifying therapy. With its strong science and translational research base, the UK is making a considerable contribution to these studies.